KOMPETENSI GURU PAI DALAM PENGEMBANGAN LINGKUNGAN SEKOLAH BERWAWASAN MODERASI BERAGAMA: STUDI MULTISITUS - Nailun Nabilah; Hani’atul Khoiroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the important role of Islamic Religious Education (PAI) teachers’ competence in developing a school environment that promotes religious moderation amid the diversity of students’ social and religious backgrounds. Schools are not only institutions for transferring knowledge, but also spaces for shaping students’ character, tolerance, and inclusive attitudes. Therefore, PAI teachers are expected to possess pedagogical, personal, social, and professional competencies that support the internalization of religious moderation values within the school environment. This study aims to examine the competence of PAI teachers in developing a school environment based on religious moderation at SMAN 1 Cerme and SMPN 24 Gresik. The research employed a qualitative approach with a multisite study design. Data were collected through semi-structured interviews, observations, and documentation involving PAI teachers, school principals, and students. The findings indicate that the competence of PAI teachers plays a significant role in creating a moderate school environment through dialogical learning, exemplary behavior, harmonious social interaction, and the integration of religious moderation values into intracurricular and extracurricular activities. Pedagogical competence is reflected in teachers’ ability to design inclusive learning processes, while personal and social competencies are demonstrated through tolerant, fair, and open-minded attitudes in daily interactions. In addition, professional competence supports the strengthening of religious moderation values through contextual learning strategies. The development of a moderate school environment is also supported by school culture, leadership policies, and the participation of all school members, although challenges remain in the form of limited understanding of religious moderation and the influence of digital media